Access to library facilities and services for users with disabilities: a study of Aligarh Muslim University in India. Issue 1 (2nd January 2021) - Nazim, Mohammad; Beg, Areeba; Sarkar, Mayukh
Abstract: The purpose of this study was to assess the convenience and accessibility of library services to users with disabilities at Aligarh Muslim University in India. The study utilized both quantitative and qualitative methods through questionnaires, interview and remarks applying the IFLA checklist to investigate the scenario. The study established that AMU has a purpose-built library to accommodate users with disabilities; however, additional funds were not allocated for developing library facilities, assistive technologies and collections in the accessible formats that lead to the delivery of inadequate services to users with disabilities. Despite the availability of some specialized services, the study found that users with disabilities face numerous obstacles when using library services due to unavailability of library materials in convenient formats, lack of assistance from the trained library staff and lack of adequate training to users. The paper concludes with the recommendations to implementing guidelines of IFLA and UNESCO regarding access to library services for users with disabilities.